The location analysis of the local pharmacies by the multi criteria decision-making AHP-Fuzzy method (case study IRAN-SHIRAZ) - Mohammad Mehdi Jabbedari; Jalal Karami; Ali Sarkargar Ardekani (Fasa University of Medical Sciences, 2016)
Background & Objective: Due to the burden on citizens seeking access to the pharmacies, the optimal location of pharmacies, patients' access to medicines, and the pharmacies proportional distribution, are some significantly important factors to consider.. The main objective of this study was to evaluate the current distribution of pharmacies and to determine the best location for the establishment of new pharmacies in the study area. Materials & Methods: This study was a case study that was conducted in the city of Shiraz. This study collected data in the form of a map to locate the service centers, weighting the criteria and compare them with other test methods which were used to analyze the hierarchy in the geographical information system (GIS). The layers (maps) used  in this study were eight dual-layer maps, including 200 meters of daily pharmacies and 1000 meters of overnight pharmacies. In addition, the final weight was calculated for each layer by AHP-Fuzzy method. Results: 24 locations in the city were demonstrated, as the best places to establish a new pharmacy according to the research criteria layers. The incompatibility rate of 0.8 was calculated, which shows the weight of the layers located within the accepted range. The government hospitals and pharmacies layers are in the highest weight (23%) and the lowest weight (3%) respectively. Conclusion: By the combination layers of information on the final map, the locations were identified for the establishment of pharmacies. This study showed that the current location of pharmacies in the city of Shiraz do not match the standards and requirements.